Big Data 10th CCF Conference, BigData 2022, Chengdu, China, November 18-20, 2022, Proceedings - Li, Tianrui; Mao, Rui.; Wang, Guoyin; Teng, Fei.; Zhang, Lei.; Wang, Li.; Cui, Laizhong; Hu, Jie. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 10th CCF Conference on BigData 2022, which took place in Chengdu, China, in November 2022. The 8 full papers presented in this volume were carefully reviewed and selected from 28 submissions. The topics of accepted papers include theories and methods of data science, algorithms and applications of big data.
Searching Similar Trajectories Based on Shape -- Unsupervised Discovery of Disentangled Interpretable Directions for Layer-wise GAN -- ASNN: Accelerated Searching for Natural Neighbors -- ASNN: Accelerated Searching for Natural Neighbors -- ASNN: Accelerated Searching for Natural Neighbors -- A Data-to-Text Generation Model with Deduplicated Content Planning Searching Similar Trajectories Based on Shape -- Clustering-Enhanced Knowledge Graph Embedding -- FCI:Feature Cross and User Interest Network.
Keywords: Artificial intelligence; Data mining; Image processing-Digital techniques; Computer vision; Information technology-Management.; Artificial Intelligence; Data Mining and Knowledge Discovery; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Application in Administrative Data Processing